Hedgehog Signaling Inhibition by Smoothened Antagonist BMS-833923 Reduces Osteoblast Differentiation and Ectopic Bone Formation of Human Skeletal (Mesenchymal) Stem Cells. (21st November 2019) - AlMuraikhi, Nihal; Almasoud, Nuha; Binhamdan, Sarah; Younis, Ghaydaa; Ali, Dalia; Manikandan, Muthurangan; Vishnubalaji, Radhakrishnan; Atteya, Muhammad; Siyal, Abdulaziz; Alfayez, Musaad; Aldahmash, Abdullah; Kassem, Moustapha; et al.
Abstract : Background . Hedgehog (Hh) signaling is essential for osteoblast differentiation of mesenchymal progenitors during endochondral bone formation. However, the critical role of Hh signaling during adult bone remodeling remains to be elucidated. Methods . A Smoothened (SMO) antagonist/Hedgehog inhibitor, BMS-833923, identified during a functional screening of a stem cell signaling small molecule library, was investigated for its effects on the osteoblast differentiation of human skeletal (mesenchymal) stem cells (hMSC). Alkaline phosphatase (ALP) activity and Alizarin red staining were employed as markers for osteoblast differentiation and in vitro mineralization capacity, respectively. Global gene expression profiling was performed using the Agilent® microarray platform. Effects on in vivo ectopic bone formation were assessed by implanting hMSC mixed with hydroxyapatite-tricalcium phosphate granules subcutaneously in 8-week-old female nude mice, and the amount of bone formed was assessed using quantitative histology. Results . BMS-833923, a SMO antagonist/Hedgehog inhibitor, exhibited significant inhibitory effects on osteoblast differentiation of hMSCs reflected by decreased ALP activity, in vitro mineralization, and downregulation of osteoblast-related gene expression. Similarly, we observed decreased in vivo ectopic bone formation. Global gene expression profiling of BMS-833923-treated compared to vehicle-treated control cells, identified 348 upregulated and 540 downregulated genes with significant effects on multiple signaling pathways, including GPCR, endochondral ossification, RANK-RANKL, insulin, TNF alpha, IL6, and inflammatory response. Further bioinformatic analysis employing Ingenuity Pathway Analysis revealed significant enrichment in BMS-833923-treated cells for a number of functional categories and networks involved in connective and skeletal tissue development and disorders, e.g., NF κ B and STAT signaling. Conclusions . We identified SMO/Hedgehog antagonist (BMS-833923) as a powerful inhibitor of osteoblastic differentiation of hMSC that may be useful as a therapeutic option for treating conditions associated with high heterotopic bone formation and mineralization.